Glossophobia among engineering learners: a case study at a technical university / Subatira Balakrishnan, Nurlisa Loke Abdullah and Linda Khoo Mei Sui - Balakrishnan, Subatira; Abdullah, Nurlisa Loke; Khoo, Linda Mei Sui (Universiti Teknologi MARA, 2022)
Glossophobia or fear of public speaking is commonly experienced by tertiary learners during classroom presentations. This study intends to examine the speech anxiety level experienced by engineering learners and the relationship between the learners’ English language proficiency and their speech anxiety. The study will also identify the causes of public speaking anxiety among these engineering learners. The samples were 65 Engineering Diploma students who responded to McCroskey’s Personal Report of Public Speaking Anxiety (PRPSA) questionnaire. The students’ English language grades at SPM level were used as the measurement of their English language proficiency. The findings showed the students’ speech anxiety is at moderate level (M= 105.9) and there was a weak negative relationship between total PRPSA scores and SPM English language grades (r = -.149, n = 65, p > 0.05). Mere thoughts of presenting a speech with undue worries of being asked questions were the causes of their speech anxiety. Therefore, it is proposed engineering learners be given ample public speaking trainings through planned programmes and engineering curriculum planners include elements of public speaking in engineering subjects. Public speaking skills will be an added value and increase engineering graduate employability in future.